Pengaruh Overlap Ratio pada Model Turbin Savonius terhadap Karakteristik Koefisien Daya Berdasarkan Eksperimen Pada Wind Tunnel - M. Luthfi Artia; U G S Dinata; Gusriwandi Gusriwandi; Ruzita Sumiati (Jurnal Teknik Mesin, 2022)
Wind energy is a resource that is abundant, environmentally friendly, and renewable, therefore it has the potential to be developed. Savonius vertical axis type is suitable for application in low wind speed conditions. The Savonius wind turbine has good self-starting so that it is able to rotate the rotor even though the wind speed is low, besides that the torque it produces is relatively high. This study aims to determine how differences in OR affect the performance of Savonius turbines with an aspect ratio (AR) of 2. The experimental method was applied in this research to investigate the characteristic Cp of the model using the wind tunnel with different overlap ratios of 0.1, 0.15, 0.2, 0.25, and 0.3. The wind turbine model that has been made using a 3D printing process made of PLA + material. The results obtained in each OR test are the maximum Cp value for the variation OR 0.1, which is 0.121, OR 0.15, the maximum Cp value obtained is 0.213, OR 0.2, the maximum Cp value is 0.245, OR 0.25, the maximum Cp value is 0.224 and OR 0.3, the maximum Cp value is 0.210. Based on the five overlap variations, the maximum Cp ratio is obtained at OR = 0.2, namely Cp = 0.245 and TSR = 0.7. The OR value of 0.2 is able to maximize turbine power and minimize negative torque because the flow through the overlap area can maximally direct wind power to the maximum backward blade.